THE INFLUENCE OF VILLAGE FUNDS ON THE VILLAGE DEVELOPMENT INDEX IN GRESIK REGENCY - Dewien Nabielah Agustin; Rizky Trisna Putri; Sarah Nita Hasibuan; Ian B. Arcega (Jurnal Analisa Sosiologi, 2025)
Since the enactment of Law No. 6 of 2014, villages have received funds directly from the central government. In practice, village funds are subject to a number of binding regulations that have altered the established practices of village fund management, significantly impacting fund management at the grassroots level. The method used in this study is quantitative descriptive analysis to compare village fund management before and after the Village Law, as well as quantitative methods to determine the relationship between village funds and the increase in the Village Development Index in Gresik Regency. In this study, researchers found a positive relationship between increases in village funds and increases in the Village Development Index (IDM). The regression coefficient for village funds was 0.64, indicating a positive influence on the Village Development Index. However, this influence is small. Therefore, it can be concluded that village funds have an influence on increasing the Human Development Index (HDI) in Gresik Regency. Consequently, in accordance with Bourdieu’s theory, it is emphasized that the distribution of village funds does not merely increase the index but also creates opportunities for social transformation.